HOLISTIC STRATEGY FOR IMPROVING BANK JATIM EMPLOYEES’ PERFORMANCE: THE ROLE OF REWARDS AND TRAINING WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Moch. Farid Afandi; Dwiyani Sudaryanti; Siti Asiyah (Pena Cendekia Insani, 2025)
Abstract: The increasingly intense competition in the modern banking industry demands strategic human resource (HR) management to maintain competitive advantage. The success of financial institutions, particularly Bank Jatim as one of the largest regional development banks in Indonesia, is determined not only by asset and profit growth but also by the quality of employee performance, as they serve as the frontline in delivering services. Internal challenges such as the effectiveness of reward programs, the relevance of training, and variations in employee work motivation have the potential to affect the company’s target achievement, despite positive trends in financial indicators. This study aims to analyze the effect of rewards and training on employee performance at Bank Jatim, Lumajang Branch, with work motivation as an intervening variable. The study employs a quantitative approach with an explanatory research design, involving 127 employees as respondents. Data were collected using a 5-point Likert scale questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 3.0. The results indicate that rewards and training have a significant positive effect on employee performance, while work motivation does not significantly affect performance nor mediate the influence of the two variables. Rewards have the strongest effect through interpersonal recognition, while training is more impactful through instructor quality, though the relevance of training materials still needs improvement. Work motivation tends to be high in terms of self-actualization but low in terms of job security, thus limiting its contribution to performance.